2003
DOI: 10.2307/30040691
|View full text |Cite
|
Sign up to set email alerts
|

The Social Side of Creativity: A Static and Dynamic Social Network Perspective

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Academy of Management is collaborating with JSTOR to digitize, preserve and extend access to The Academy of Management Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
564
3
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(616 citation statements)
references
References 48 publications
(83 reference statements)
15
564
3
13
Order By: Relevance
“…Taken together, boundary-spanning creates an opportunity for both TMs and MMs to access a variety of different perspectives and information flows throughout the organization (Perry- Smith and Shalley 2003;Tsai and Ghoshal 1998), allowing both levels to achieve higher levels of exploratory innovation within their units (Rogan and Mors 2014). However, given their different role requirements, authority and varying degrees of resource access, the relationship between boundary-spanning and exploratory innovation is expected to be stronger for TMs than for MMs.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, boundary-spanning creates an opportunity for both TMs and MMs to access a variety of different perspectives and information flows throughout the organization (Perry- Smith and Shalley 2003;Tsai and Ghoshal 1998), allowing both levels to achieve higher levels of exploratory innovation within their units (Rogan and Mors 2014). However, given their different role requirements, authority and varying degrees of resource access, the relationship between boundary-spanning and exploratory innovation is expected to be stronger for TMs than for MMs.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Exploratory innovation requires new knowledge (Benner and Tushman 2002) and is facilitated when a work environment promotes risktaking and provides knowledge-rich stimuli and sufficient resources (Amabile et al 1996;Jansen et al 2012). Managers who span boundaries thus encounter a wider range of people with different outlooks and approaches (Perry-Smith and Shalley 2003) and may find it easier to navigate and nurture their entrepreneurial projects despite organizational politics (Lechner et al 2010). In fact, recent studies suggest that interactions with members of internal and external networks enable MMs to gain the support they need to protect their entrepreneurial activities and leverage their credibility (Morris et al 2010) as well as legitimacy (Hornsby et al 2013).…”
Section: Boundary-spanning and Strategic Renewalmentioning
confidence: 99%
“…For example, Baer (2014) argued for the strength-of-weak ties perspective in creativity (see also Brass, 1995;Perry-Smith 2006;Perry-Smith & Shalley, 2003;Zhou, Shin, Brass, Choi & Zhang, 2009) and found that actors are more creative in idea networks of optimal size, weak strength, and high diversity, and when they score high on openness to experience. Similarly, Perry-Smith (2014) in an experimental study found tie strength to affect creativity through individual processing of non redundant knowledge.…”
Section: Ethical Leader Behaviorsmentioning
confidence: 99%
“…Following this line of thought and drawing more explicitly from research by sociologists and sociopsychologists (Kavolis 1966, Simonton 1984a, organizational scholars have recently started to investigate the network side of individual creativity (Perry-Smith and Shalley 2003, Burt 2004, Perry-Smith 2006. The key idea of this emerging perspective is that a deeper understanding of how creative outputs are generated "demands that the creative individual be placed within a network of interpersonal relationships" (Simonton 1984a(Simonton , p. 1273.…”
Section: Introductionmentioning
confidence: 99%